VPM1002 as Prophylaxis Against Severe Respiratory Tract Infections Including Coronavirus Disease 2019 in the Elderly: A Phase 3 Randomized, Double-Blind, Placebo-Controlled, Multicenter Clinical Study. (11th November 2022) - Blossey, Alexandra M; Brückner, Sina; May, Marcus; Parzmair, Gerald P; Sharma, Hitt; Shaligram, Umesh; Grode, Leander; Kaufmann, Stefan H E; Netea, Mihai G; Schindler, Christoph
Abstract: Background: Bacille Calmette-Guérin (BCG) vaccination can potentially reduce the rate of respiratory infections in vulnerable populations. This study evaluates the safety and efficacy of VPM1002 (a genetically modified BCG) as prophylaxis against severe respiratory tract infections including coronavirus disease 2019 (COVID-19) in an elderly population. Methods: In this phase 3, randomized, double-blind, placebo-controlled, multicenter clinical trial, healthy elderly volunteers (N = 2064) were enrolled, randomized (1:1) to receive either VPM1002 or placebo, and followed up remotely for 240 days. The primary outcome was the mean number of days with severe respiratory infections at hospital and/or at home. Secondary endpoints included the incidence of self-reported fever, number of hospital and intensive care unit (ICU) admissions, and number of adverse events. Results: A total of 31 participants in the VPM1002 group reported at least 1 day with severe respiratory disease and a mean number of days with severe respiratory disease of 9.39 ± 9.28 while in the placebo group; 38 participants reported a mean of 14.29 ± 16.25 days with severe respiratory disease. The incidence of self-reported fever was lower in the VPM1002 group (odds ratio, 0.46 [95% confidence interval, .28–.74]; P = .001), and consistent trends to fewer hospitalization and ICU admissions due to COVID-19 were observed after VPM1002 vaccination. Local reactions typical for BCG were observed in the VPM1002-vaccinated group, which were mostly of mild intensity. Conclusions: Vaccination with VPM1002 is well tolerated and seems to have a prophylactic effect against severe respiratory disease in the elderly. Clinical Trials Registration: NCT04435379. Abstract : This elderly study population showed fewer days with respiratory tract infections when vaccinated with VPM1002. A lower incidence of self-reported fever and consistent trends toward a reduction in hospitalizations and ICU admissions due to COVID-19 were seen compared to placebo.